SiCi_xNxthin films preparation by TEA-Co2 Laser induced Vapor-phase reaction and study of the nature of chemical bonds and some their electrical and optical properties - Baghdad Science Journal (مجلة بغداد للعلوم)
A pulsed (TEA-0O2) laser was used to dissociate molecules of silane ethylene (C2I-14) and ammonia (NH3) gases, through collision assisted multiple photon dissociation (MPD) to deposit(SiC i_xNx) thin films, where the X-values are 0, 0.13 and 0.33, on glass substrate at T,----648 K. deposition rate of (0.416-0.833) nm/pulse and thickness of (500-1000)nm .Fourier transform infrared spectrometry (FT-IR) was used to study the nature of the chemical bonds that exist in the films. Results revealed that these films contain complex networks of the atomic (Si, C, and N), other a quantity of atomic hydrogen and chemical bonds such as (Si-N, C-N, C-14 and N-H).Absorbance and Transmittance spectra in the wavelength range (400-1100) nm were used to study the optical properties of the deposited films. It was found the optical nergy ap E0) of these films is indirect and increases with increasing (X) while the width of localized states decreases.The study of the electrical properties of the deposited films revealed that their electrical conductivity at any constant temperature decreases with increasing (X) and the films have two activation energies both increase with increasing (X).